2019
DOI: 10.1097/phh.0000000000001061
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Hepatitis C Virus Telehealth Services Serving Tribal Communities: Patterns of Usage, Evolving Needs, and Barriers

Abstract: Introduction: American Indian/Alaska Native (AI/AN) populations are disproportionately affected by chronic hepatitis C virus (HCV) infection. Federal facilities of the Indian Health Service, in conjunction with Tribally operated and Urban Indian (I/T/U) health care facilities, serve an estimated 2.2 million AI/AN patients. The facilities are mainly rural and have few specialists. To fill the gap in specialists in I/T/U clinics, the Extension for Community Healthcare Outcomes (ECHO) telehealth model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…A survey of 44 clinicians who participated in Indian Country ECHO cited that the continued barriers to HCV treatment were lack of access to HCV medications, need for more frequent/regular access to specialists, difficulty getting patients into care/follow-up, and limited clinical time for HCV. 25 Access to HCV treatment medication was noted as a…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of 44 clinicians who participated in Indian Country ECHO cited that the continued barriers to HCV treatment were lack of access to HCV medications, need for more frequent/regular access to specialists, difficulty getting patients into care/follow-up, and limited clinical time for HCV. 25 Access to HCV treatment medication was noted as a…”
Section: Discussionmentioning
confidence: 99%
“…25 and at least one of the following: platelet counts less than 150,000/mm3 , FibroSure®/FibroTest result indicating cirrhosis, or imaging results demonstrating cirrhosis. Patients with cirrhosis were compared to patients without fibrosis and patients with indeterminant fibrosis.…”
mentioning
confidence: 99%
“…Telemedicine-based models have been used more frequently in other settings to optimize the care cascade for HCV-infected patients [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Recently, independent studies have shown how the support of telemedicine improve the access and management of antiviral treatment in the Department of Corrections, optimizing therapy effectiveness [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Treatment Modelsmentioning
confidence: 99%
“…Similarly, telemedicine has also been successfully used to implement the HCV care cascade in remote areas, where the usual management and treatment models would have meant significant logistical difficulties, long waiting times, and high costs [ 54 , 55 , 56 , 57 , 58 ].…”
Section: Treatment Modelsmentioning
confidence: 99%
“…Because of a variety of social and geographical factors (eg, marginalization of patients with chronic hepatitis C, a high prevalence of hepatitis C in prisoners, limited access to specialty care in traditionally medically underserved communities), treatment of chronic hepatitis C has historically been challenging. ( 13,14 ) According to the World Health Organization, an estimated 71 million people have chronic hepatitis C; however, of those diagnosed with hepatitis C, only 5 million have been treated with direct‐acting antivirals by the end of 2017. ( 15 ) It is believed that a primary reason for the discrepancy in the number of patients with chronic hepatitis C and the number of patients receiving treatment is the lack of access to treatment in many parts of the world.…”
Section: Use Of Telemedicine In Hepatologymentioning
confidence: 99%